MERCURY SPECIATION AND DISSOLVED ORGANIC CARBON CHARACTERIZATION IN THE SURFACE WATERS OF SEPETIBA BAY, SE BRAZIL - Paraquetti, H. H. M.; Lacerda, L. D.; Ayres, G. A.; Mounier, S.; Almeida, M. D. (Geochimica Brasiliensis, 2012)